Peningkatan Literasi Keuangan Kepada Pengusaha Kerajinan Ketak Melalui Pelatihan Pencatatan dan Pembukuan - Nurul Hidayati Indra Ningsih; Baiq Reinelda Tri Yunarni; Dedy Iswanto (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The craft of woven skin is one of the typical handicrafts of Lombok. In Batu Mekar Village, there are around 600 people who work as craftsmen of weaving. The main problem faced by plaited woven entrepreneurs is related to financial management. This service activity aims to provide an understanding of the importance of making financial records and bookkeeping. Methods of implementation of service activities used in this service, namely observing how the knowledge of woven businessmen about recording and accounting of their business finances, socializing the importance of carrying out financial records and bookkeeping in running a business and providing understanding and training on the importance of carrying out financial records and bookkeeping in running effort. The result of this activity, namely the bookkeeping and financial recording training activity, is like a breath of fresh air for local entrepreneurs and craftsmen, how can the efforts made in this activity provide a broad description of how to diversify the process of moving downstream of the weaving tack. From this dedication activity, the craftsmen groups are not eager to seriously form groups in order to maximize the results of their efforts.